Individual Growth And Gonad Development Of Female Tilapia (Oreochromis Sp.) With Addition Of Velvet Bean (Mucuna Pruriens) Seed Extract - Ahmad Shofy Mubarak; Kamiliya Zahrah Taher; Putri Eriza Riyanto; Akhmad Taufiq Mukti; Muhamad Amin; Syifania Hanifah Samara (Airlangga University, 2023)
Tilapia is one of the fish that is widely cultivated in Indonesia. The obstacle to tilapia cultivation is high reproduction, which inhibits growth. An alternative to increase growth is by inhibiting gonad growth, so that feed energy is focused on somatic development. The aim of this research was to analyse the effect of velvet bean extract concentration on individual growth and gonad development of female tilapia fish and to determine the optimum concentration of velvet bean extract to increase growth and reduce reproductive activity in female tilapia fish. This study used a Completely Randomized Design (CRD) with the addition of various velvet bean extracts and compared with the control (without velvet bean extract). The use of velvet bean extract had a significant effect (p<0.05) on growth parameters such as length, weight, fecundity and egg diameter. The best treatment was found in treatment 3 (velvet bean extract 5 ml.kg-1 ) which resulted in growth in individual length of 16.1 cm, individual weight of 89.43 g, fecundity of 2206 and egg diameter of 1.11 mm. In addition, the dose in this treatment may reduce the reproductive activity of tilapia.